30th Congress of the Italian Society of Neonatology - Lombardy section | Bergamo, 3-4 February 2017 - Luciano Musi; Alessandro Frigiola; Marcello Giovannini; Luca Rosti (PAGEPress Publications, 2017)
This abstract book contains the abstracts presented at the 30th Congress of the Italian Society of Neonatology - Lombardy section | Bergamo, 3-4 February 2017.